THE EFFECT OF TAX FAIRNESS, TAX UNDERSTANDING, AND TAX COLLECTION ON THE TAX COMPLIANCE OF INDIVIDUAL TAXPAYERS WHO ARE EMPLOYEES - Maharani, Nabila; Ridwansyah, Eksa; Anggraini, Depita (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This study aims to examine the influence of Tax Fairness, Tax Understanding, and Tax Collection on Tax Compliance among Individual Employee Taxpayers at the Palembang Ilir Barat Pratama Tax Office (KPP Pratama). This study used a quantitative descriptive approach with primary data obtained through questionnaires and processed using SPSS. The results indicate that Tax Fairness, Tax Understanding, and Tax Collection have a positive and significant influence on Tax Compliance among Individual Employee Taxpayers. It is recommended that the government and the Directorate General of Taxes increase transparency and accountability in tax management to strengthen perceptions of fairness. Furthermore, individual taxpayers should improve their tax literacy and understanding, particularly regarding the obligation to report Annual Tax Returns, filing procedures, and applicable administrative sanctions.